1996
DOI: 10.1515/reveh.1996.11.4.175
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Health Implications of Heavy Metal Pollution from Car Tires

Abstract: This paper reviews the potential for environmental pollution by heavy metals from the disposal of used car tires and describes laboratory work and field research exploring the magnitude of the problem. The metals considered here are cadmium, lead, and zinc; their respective mean concentrations for ten makes of tires used in the United Kingdom ranged from 0-3.0, 8.1-22.3, and 2524-6012 ppm. The metals were extracted from tires by simulated acid-rain solutions (pH 2.5); zinc concentrations of the leachate ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 6 publications
1
22
0
4
Order By: Relevance
“…Although geographic distribution suggested a propensity to higher BLLs with proximity to major roads, statistical analysis did not produce evidence of this a priori possible association (because of relatively recent use of leaded gasoline). The prevalence of lead metal within tires in Uganda is not known, but other studies have shown that this can contribute to increased soil lead levels near roadways (Horner 1996). Major roads also emanate from the landfill and thereby complicate disaggregation of effects relating to living near roads where old leaded dust may be resuspended by vehicles from effects relating to water contamination from the landfill.…”
Section: Discussionmentioning
confidence: 99%
“…Although geographic distribution suggested a propensity to higher BLLs with proximity to major roads, statistical analysis did not produce evidence of this a priori possible association (because of relatively recent use of leaded gasoline). The prevalence of lead metal within tires in Uganda is not known, but other studies have shown that this can contribute to increased soil lead levels near roadways (Horner 1996). Major roads also emanate from the landfill and thereby complicate disaggregation of effects relating to living near roads where old leaded dust may be resuspended by vehicles from effects relating to water contamination from the landfill.…”
Section: Discussionmentioning
confidence: 99%
“…ZnO particles in ambient air arise from incinerator emission and from wear and tear of vehicle tires (Adachi and Tainosho 2004; Bennett and Knapp 1982; Councell et al 2004; Horner 1996; Lough et al 2005). Previous studies have demonstrated that exposure to Zn-laden (Zn in its salt and oxidized forms) ambient particles contribute to the increase in bronchitis and asthma morbidity and in lung toxicity (Adamson et al 2000, 2003; Hirshon et al 2008; Pope 1989).…”
mentioning
confidence: 99%
“…On the other hand, zinc is also a common airborne metallic contaminant that derives from combustion, tire wear, and industrial processes that may contribute to the adverse health effects of ambient pollution (1,2,9,10,17 (31,(51)(52)(53)(54)(55), the regulation of COX-2 expression by these activities in Zn 2ϩ -treated cells has not been characterized. This study characterizes the association of these intracellular signaling pathways with Zn 2ϩ -induced COX-2 expression in human bronchial epithelial cells and their cross talk during this event.…”
mentioning
confidence: 99%